Evaluasi Program Ekstrakurikuler Pramuka Sekolah Menengah Kejuruan - Heni Triana; - Wasitohadi; Bambang Ismanto (Kelola: Jurnal Manajemen Pendidikan, 2020)
The purpose of this study was to evaluate the scout extracurricular program at SMK Telekomunikasi Tunas Harapan. This research is included in qualitative evaluative research with Kirkpatrick's evaluation model which consists of four stages, namely: reaction, learning, behavior and results. The research subjects included 1 principal, 2 scout coaches, 4 teachers, and 77 class X students. Data collection techniques were through filling out questionnaires, observation, interviews, and documentation study. The stages taken in the data analysis process include: data collection, data reduction, drawing conclusions, data presentation. The data validation used triangulation of data sources and triangulation of data collection techniques. The results of this study indicate that: (1) at the reaction evaluation stage with a percentage of 87.88% included in the "very good" category, students who took scout extracurricular activities were satisfied with the material, the attitude of the trainer, the knowledge of the trainer, the media, methods and facilities of scouting education. . (2) At the learning evaluation stage with a percentage of 83.68% included in the "good" category, the student response at the learning stage showed that the student's attitude responded positively to scout extracurricular activities. (3) At the behavior stage with a percentage of 83.11% included in the "good" category, after participating in scout extracurricular activities, students showed changes in behavior (4) At the results stage with a percentage of 83.83% included in the "good" category the scout extracurricular program showed results. Positive, students become more disciplined, independent, responsible, cooperative and religious. The results showed that the scout extracurricular program showed success with an average value of all components of 84.62% including in the good category.